Mullerian inhibiting substance expression in papillary thyroid cancer - Girgin, Mustafa; Kilinc, Gokhan Sami; Ozercan, Ibrahim; Simsek, Bengu Cobanoglu; Kavak, Burcin; Celik, Husnu; Kanat, Burhan Hakan (Elsevier Singapore Pte Ltd, 2013)
Objective: To examine the expression of Mullerian inhibiting substance (MIS) in papillary thyroid cancer. Materials and methods: The MIS expression was examined by studying the immunohistochemistry in deparafinized sections prepared from tissue blocks of patients who were diagnosed with papillary thyroid cancer, as given in the pathology archive records (n = 23). Results: In all the cases studied, 50% (n = 10) showed strong staining and 50% showed moderate staining. The percentage of staining was found to be 94.2 +/- 3.1% in strongly stained cases and 92.2 +/- 2.1% in moderately stained cases. Normal thyroid tissues neighboring the tumor did not display any staining. Conclusion: The MIS expression can be used as a significant tool in differential diagnosis of papillary thyroid cancer and also to shed light on its etiopathogenesis. Copyright (C) 2012, Asian Surgical Association. Published by Elsevier Taiwan LLC. All rights reserved.
Keywords: immunohistochemistry; Mullerian inhibiting substance; papillary thyroid cancer